Predictive factors for HbA1c and weight loss associated with semaglutide treatment in type 2 diabetes mellitus: real-world clinical evidence - Milushewa, Petya; Mitreva, Yoanna; Chakarova, Nevena; Tankova, Tsvetalina; Naseva, Emilia; Petkova, Valentina (Frontiers in Endocrinology, 2025)
ObjectiveThis study aimed to identify clinical predictors associated with reductions in HbA1c and weight among patients with type 2 diabetes mellitus (T2DM) treated with semaglutide in real-world clinical settings in Bulgaria.MethodsA retrospective analysis was conducted on 168 T2DM patients receiving dispensary monitoring at the University Specialized Hospital for Active Treatment in Endocrinology “Acad. Ivan Penchev,” Sofia. Clinical data, including comorbidities, HbA1c, weight, and BMI, were collected from medical records at baseline and after one year of treatment. Patients were administered subcutaneous semaglutide beginning at 0.25 mg weekly, titrated to 0.5 mg after four weeks, and to 1 mg thereafter, maintained over a one-year period.ResultsAt baseline, 92.3% of patients had obesity (BMI ≥30 kg/m²), with 53.6% categorized as Obesity Class 1. After one year of GLP - 1RA therapy, significant improvements in metabolic parameters were observed. Median weight reduced from 100.0 kg to 91.5 kg (p<0.001), and median BMI decreased from 33.6 to 30.9 kg/m² (p<0.001). HbA1c levels declined from 7.80% to 6.90% (p<0.001). Transitions to lower obesity classes occurred in 81 patients, while 15 remained in Class 3 obesity.ConclusionsSemaglutide significantly improves glycemic control and promotes weight and BMI reduction in T2DM patients in routine clinical practice. These findings suggest that structured follow-up under endocrinologist supervision, as required by national protocols, may enhance therapeutic response. Further prospective studies with extended follow-up are warranted to evaluate the long-term sustainability of these effects and to identify predictors of optimal patient response.